2021
DOI: 10.1016/j.jds.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Semi-fixed versus fixed oral appliance therapy for obstructive sleep apnea: A randomized crossover pilot study

Abstract: Background/purpose Although mandibular advancement oral appliances (OAs) are the most widely used and accepted therapeutic modality for obstructive sleep apnea (OSA), whether these maxillary and mandibular appliances should be semi-fixed or fixed remains uncertain. This randomized crossover pilot study compared the efficacy, side effects, and patient preference of semi-fixed and fixed OAs for the treatment of OSA. Materials and methods Patients with mild to moderate OSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…After a full‐text review, 42 studies with 2265 patients of OA were included for Meta‐analysis. The included studies included 6 TRD, 14‐19 and 35 MAD 20‐54 literature. In addition, Barthlen et al 55 incorporated both TRD and MAD.…”
Section: Resultsmentioning
confidence: 99%
“…After a full‐text review, 42 studies with 2265 patients of OA were included for Meta‐analysis. The included studies included 6 TRD, 14‐19 and 35 MAD 20‐54 literature. In addition, Barthlen et al 55 incorporated both TRD and MAD.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors in their studies have concluded that MAD has a good contribution in reducing AHI and in raising the quality of life in such patients when compared with CPAP [12,13]. MAD works on the principle of clasping the mandible in a forward and downward position that helps to reduce AHI by enlarging the upper airway [14].…”
Section: Introductionmentioning
confidence: 99%